Environmental Resilience in Arabic Literature: Eco-critical Readings of al-Wabā’ and al-Maṣābīḥ al-Zurq and Their Relevance for Sustainable Rural Development - Teguh Luhuringbudi; Achmad Satori Ismail; Fitri Liza (RaSAIL Media Group, Semarang, Indonesia, 2025)
This study analyzes the representation of environmental resilience in two modern Arabic novels—Hānī al-Rāhib's Al-Wabā' and Ḥannā Mīnah's al-Maṣābīḥ al-Zurq—by focusing the unit of analysis on narrative elements such as characters, settings, symbolic events, and ecological metaphors that describe the community's response to environmental pressures. The purpose of this research is to explore how the representation of literature can enhance the understanding of sustainability dynamics relevant to rural development. Using a qualitative-descriptive method, this study applies three analytical approaches: ecocriticism, environmental sociology, and the Sustainable Livelihoods Framework. The findings suggest that figures such as al-Shaikh and Sheikh Abdel Jawad represent a shift away from traditional agrarian values to new forms of adaptation shaped by political instability, resource scarcity, and changes in social structures. Both novels reveal patterns of vulnerability, resilience, and livelihood strategies that reflect real processes in dealing with environmental changes. The contribution of this research lies in the designation of the role of literary works as a medium that reflects ecological pressures, as well as a conceptual tool that can enrich cross-disciplinary discussions on sustainability and provide interpretive insights that complement empirical studies of rural development.